Mothers' treatment styles and their relationship with self-confidence in diabetic children - Al-Nosayan, Hessa Suliman; El-Gabry, Asmaa (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the relationship of mother's treatment styles and its relationship with self-confidence in diabetic children.A sample of 50 mothers of diabetic children whose ages ranged from 25 to 35 years old and whose education levels ranged from secondary to university level were studied with a descriptive approach and correlation method. Twenty-five of the children were male and the other 25 were female. Their ages ranged from three to six years, and they were deliberately selected from King Khalid University Hospital in Riyadh.The researcher has adopted the following instruments:- The scale of mother's treatment styles.- Self-confidence scale in diabetic children.Below listing nine proven hypothesis during this study:- There is a statistically significant correlation between the average scores of maternal treatment methods and the average score of self-confidence in diabetic children.- There is a direct statistical correlation with a significance level (0.01) between the balanced approach in mother's treatment style and self-confidence in diabetic children.- There is a direct statistical correlation with a significance level (0.01) between the independence in mother's treatment style and self-confidence in diabetic children.- There is an inverse statistical correlation with a significance level (0.01) between the rejection method in mother's treatment style and self-confidence in diabetic children.
Keywords: maternal treatment methods; self-confidence; children and diabetes